TARI TAYUB SEBAGAI SARANA UPACARA RITUAL DI DESA WONOSOCO KECAMATAN UNDAAN KUDUS - Suharji, Suharji (Institut Seni Indoensia Surakarta, 2014)
Wonosoco village, district of Undaan, Kudus has a unique tradition called ritual after planting paddyby farmers. This ritual is arranged by a group of three farmers to expel paddy’s pest symbolicallyespecially rat. This research aims to: a) describe ritual ceremony which uses tayub dance as its toolsin Wonosoco, b) describe factors that support ritual of tayub performance, c) write down a journalarticle. For that reasons, this research uses inductive descriptive analytical method with qualitativedata. There are some steps in research writing included data sampling based on field study, observationof tayub performance, interview with guest speaker and informant. For data processing, it usesserial triangulation system such as data reduction, data reformation or data display, and conclusion.This research also uses dance sociological method (as a science that concerns with correlation amongsociety, dance, and its artist).The findings of this research show that dance performance has major meaning in terms of gratitudeand demand to God for giving people bless, being restraint from trouble, granting for all prays, andall of soul as village’s guardian feel happy so increase interest for working hard and reach success.Tayub dance performance that has taken place during four years has been ritual, association, andfriendship tools and has given an entertainment to make life balance.Keywords: dance, tayub, ritual ceremony.